MATHEMATICAL UNDERSTANDING OF MIDDLE SCHOOL STUDENTS ACCORDING TO DIFFERENT VARIABLES - Yasemin KABA (Fırat University, 2019)
According to Pirie-Kieren, mathematical understanding, which is developed as a result of a complex movement that requires going back and forth on the understanding layers, is a self-renewing process. Determination of factors affecting this complex-structured process may help to comprehend mathematical understanding. Therefore, it is intended to examine mathematical understanding of the middle school students according to different variables (gender, grade, success, etc.) in this research. The research is a descriptive study in a survey model. 807 students studying in two state middle schools in İzmit district of Kocaeli province constitute the study group. “Personal Information Form” (PIF)” and “Determining the Mathematical Understanding Levels Scale (DMULS)” are used as data collection tools. According to the research results, it is revealed that mathematical understanding of the female students is higher than the male students. It is determined that as the grade rises, mathematical understanding decreases and as the academic achievement increases, mathematical understanding increases too. While it is determined that receiving help or not during studying does not create any difference on the mathematical understanding, it is revealed that having an in